The analysis of selected aspects of satisfaction with hospitalization of hemispheric brain damage patients - Wasilewski, Tadeusz Paweł (Polish Journal of Public Health, 2009)
The enquiry into satisfaction of the hospitalized patients is a traditional way of the assessment of the quality of health care. This is an exceptionally valuable technique of medical service verification. Thanks to such types of assessment a therapeutic team obtains information on the level of rendered service (care), meeting expectations and patients’ needs and problem solving. The assessment of patients’ satisfaction also allows us to feel the signs of distress of clients in terms of medical service.The goal of the presented study is a subjective assessment of the selected aspects of satisfaction with hospitalisation. This evaluation was made by the patients with hemispheric brain damage compared to the control group. The investigation was conducted in 2004 among 173 hospitalised clients at the Neurology and Children’s Neurosurgery and Neurology Department of Independent Public University Hospital No.4 of Medical University of Lublin. To carry out the assessment, a Questionnaire of Patient’s Satisfaction of Hospital Stay was used. The following aspects were considered in the questionnaire ensuring religious needs, making contacts with family and informing patients.The findings revealed that nearly half of the clients of each treated group knew a departmental nurse and a lower percentage of the sick identified the nurse who took care of a particular group of patients. The study showed that about 70 percent of patients from each group were informed about their rights. The statistical analysis of acquired results emphasized a high level of aspect with regard to ensuring religious needs and a contact with a family. The study also indicated that 90% of patients from the experimental groups and the control one expressed their satisfaction with care.